Taiwan and the Rise of China : Cross-Strait Relations in the Twenty-first Century. - Guo, Baogang (Challenges facing Chinese political development., 2012)
Taiwan and the Rise of China examines one of the fast evolving, yet very volatile, fragile and asymmetric, bilateral relations in East Asia. The insightful analyses provided by the experts of China studies should be of great interest to scholars, students and policy makers.